From the Scholarship of Teaching and Learning to the Scholarly Institution: A STEM Perspective - Collins, Trevor D.; Butler, Diane; Gretton, Sarah; Williams, Neil (Teaching and Learning Inquiry, 2025)
There has been a documented increase in SoTL activity, which in the United Kingdom (UK) may be a result of the heightened focus on teaching due to increased regulation and monitoring, competition, changes in the workforce structure, and quality enhancement within the sector. STEM academics specifically face challenges in engaging with SoTL as the methodologies used differ from their discipline training. Offering a STEM perspective, we provide four case studies at the institutional and national level of interventions in STEM teaching to address these challenges, namely: conducting educational research with students as partners, establishing a faculty based SoTL centre, reward and recognition of staff, and the formation of a national SoTL conference for STEM educators. We discuss the extent to which the case studies demonstrate Felton’s principles of good scholarship and propose the concept of a “scholarly institution” as one which systematically nurtures and harvests SoTL research (internal and external to the institution) by establishing structures and cultures that foster evidence-informed teaching and learning practices. We conclude that to truly realise the benefits of SoTL, practitioners not only need support to undertake SoTL inquiries, but that the institutions must commit to using SoTL to inform their policies and procedures as well.